Types of chronic diseases associated with sedentary behaviour and physical inactivity - Mandili, Ibtisam M.; Balobaid, Abdulrahman N.; Alzahrani, Hadeel H.; Almalki, Mamdouh A.; Alghamdi, Ahmed A.; Alaradi, Rema R.; Fallatah, Haifa B.; Alzahrani, Wijdan H.; Alamri, Habeeb Z.; Eid, Sami S. (International Journal Of Community Medicine And Public Health, 2022)
Chronic disease causes a global burden of significant morbidity and mortality. The onset of many chronic diseases is strongly connected with lifestyle variables including physical inactivity. Chronic diseases were previously more prevalent in older population however they are increasingly now becoming more common among young adults and adults due to lifestyle modifications The prevalence of sedentary behaviour and the rise in non-communicable diseases it causes are a universal phenomenon. Physical inactivity is the fourth most important risk factor for mortality and accounts for 6% of all deaths worldwide. Exercise and physical activity are now regarded as the one of the main therapies for both primary and secondary prevention of chronic diseases. The purpose of this research is to review the available information about types of chronic diseases associated with sedentary behaviour and physical inactivity. Physical inactivity is the modifiable risk factor of chronic diseases. Recent evidence suggests that physical activity plays a critical role in reducing risk and complications of prevalent chronic diseases including cardiovascular diseases, diabetes, obesity, cancers, arthritis among other chronic diseases. As per various epidemiological studies, the incidence of coronary heart disease in physically active people is almost half in comparison to the people who are sedentary. Physical activity is beneficial in the management of diabetes. Physical activity can improve physical function and quality of life in individuals with chronic diseases while decreasing the risk of disease progression and premature mortality, depending on the chronic condition and outcome.